Hubungan Metode Pembelajaran Bahasa Arab Terhadap Minat Belajar Siswa SMPIT Insan Cendekia Kampar - Amida Fazuhra; Saproni Muhammad Samin (UIR Press, 2022)
This study aims to determine the relationship between the Arabic language learning method and the students' interest in learning at SMPIT Insan Cendikia Kampar. This research is quantitative research with a correlational approach—the Researcher conducted at SMPIT Insan Cendekia Kampar. The population in this study were all 75 students of SMPIT Insan Cendekia Kampar, while the sample used was total sampling. The data collection technique used in this study is to use a questionnaire instrument for Arabic learning methods. A student learning interest questionnaire was tested to test the validity and reliability of the instrument items used in this study, using reality and reliability tests and normality tests. And linearity. The data processing technique uses SPSS 20 with editing, coding, data tabulation and scoring techniques. Analysis of the research data using Pearson product-moment correlation. The results of this study can conclude that there is no significant relationship between Arabic learning methods on student interest in learning at SMPIT Insan Cendekia Kampar because the probability value is more critical than 0.05, namely 0.463, 0.527, 0.250, 0.448, 0.452 > 0.05 then Ho is accepted. This result of research means that there is no relationship between Arabic learning methods and the learning interests of SMPIT Insan Cendekia Kampar students.